Near‐IR to Near‐IR Upconversion Luminescence in Molecular Chromium Ytterbium Salts. Issue 42 (18th August 2020) - Kalmbach, Jens; Wang, Cui; You, Yi; Förster, Christoph; Schubert, Hartmut; Heinze, Katja; Resch‐Genger, Ute; Seitz, Michael
Abstract: Upconversion photoluminescence in hetero‐oligonuclear metal complex architectures featuring organic ligands is an interesting but still rarely observed phenomenon, despite its great potential from a basic research and application perspective. In this context, a new photonic material consisting of molecular chromium(III) and ytterbium(III) complex ions was developed that exhibits excitation‐power density‐dependent cooperative sensitization of the chromium‐centered 2 E/ 2 T1 phosphorescence at approximately 775 nm after excitation of the ytterbium band 2 F7/2 → 2 F5/2 at approximately 980 nm in the solid state at ambient temperature. The upconversion process is insensitive to atmospheric oxygen and can be observed in the presence of water molecules in the crystal lattice. Abstract : Strong upconversion luminescence at 780 nm can be observed under ambient conditions after photoexcitation at 980 nm in a new ionic solid consisting of discrete Yb III ‐ and Cr III ‐complexes. The upconversion process is insensitive to atmospheric oxygen and can be observed in the presence of water molecules in the crystal lattice.